Effect of new generation medium voltage electrical stimulation on the meat quality of beef slaughtered in a Chinese abattoir. (March 2019) - Zhang, Yimin; Ji, Xiaokai; Mao, Yanwei; Luo, Xin; Zhu, Lixian; Hopkins, David L.
Abstract: In this study, a medium voltage electrical stimulation (ES) system with three parameter combinations (A: 1A, 1.55 ms pulse width, 27 s; B: 0.55A, 1 ms pulse width, 34 s; C: 0.55A, 2 ms pulse width, 20s) were applied to beef carcases ( n  = 24; 319 ± 26.4 kg), in the context of a very slow pH decline rate in the abattoir. All the ES combinations significantly accelerated the rate of pH decline (reflected by temp@pH 6.0, i.e. temperature when pH drops to 6.0), resulting in a tenderness improvement even after 14 days ageing compared to the controls. Sarcomere length was not different between treatments and controls, and it was not a contributor to the tenderness improvement, instead, physical disruption revealed by transmission electron microscopic images may have led to the improvement. Retail colour was significantly improved by either combination B or C after 7 days of ageing. Combination B shows the most promise for commercial application, however, verification on more animals is required before commercial adoption.